Pheromone Binding Protein EhipPBP1 Is Highly Enriched in the Male Antennae of the Seabuckthorn Carpenterworm and Is Binding to Sex Pheromone Components - Hu, Ping; Gao, Chenglong; Zong, Shixiang; Luo, Youqing; Tao, Jing (Frontiers in Physiology, 2018)
The seabuckthorn carpenterworm moth Eogystia hippophaecolus is a major threat to seabuckthorn plantations, causing considerable ecological and economic losses in China. Transcriptomic analysis of E. hippophaecolus previously identified 137 olfactory proteins, including three pheromone-binding proteins (PBPs). We investigated the function of E. hippophaecolus PBP1 by studying its mRNA and protein expression profiles and its binding ability with different compounds. The highest levels of expression were in the antennae, particularly in males, with much lower levels of expression in the legs and external genitals. Recombinant PBP1 showed strong binding to sex-pheromone components, suggesting that antennal EhipPBP1 is involved in binding sex-pheromone components during pheromone communication.